The Economics of Tobacco in Turkey : New Evidence and Demand Estimates - Onder, Zeynep (World Bank, Washington, DC, 2013)
Turkey has become one of the largest consumers of cigarettes, while world cigarette consumption declined by 4 percent between 1990 and 1999. The rapid increase in tobacco consumption in Turkey will cause a large increase in the burden of disease and premature death in years to come. Global evidence also shows that there is a set of policies and interventions that can be highly effective in reducing tobacco use, encouraging smokers to quit, and deterring young people from starting to smoke. This paper provides data on the role of tobacco and cigarettes in the Turkish economy. It reviews data on cigarette consumption, and cigarette production. The role of tobacco in Turkish agriculture and foreign trade is examined. Data on cigarette taxes and their contribution to government revenues are presented, and tobacco control policies in Turkey are also described.